2009
DOI: 10.1117/1.3122371
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced tissue hyperthermia mediated by gold nanoparticles: toward cancer phototherapy

Abstract: We describe an application of plasmonic silica/gold nanoshells to produce a controllable laser hyperthermia in tissues with the aim of the enhancement of cancer photothermal therapy. Laser irradiation parameters are optimized on the basis of preliminary experimental studies using a test-tube phantom and laboratory rats. Temperature distributions on the animal skin surface at hypodermic and intramuscular injection of gold nanoparticle suspensions and affectations by the laser radiation are measured in vivo with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 36 publications
1
146
0
3
Order By: Relevance
“…In these studies, the absorption properties of gold nanorods in the surface plasmon resonance wavelength are used to elevate temperature to 50°C and above, usually using lasers with a high optical output (above 10 W/cm 2 for about 20 minutes) in order to achieve effective denaturation and coagulation of cellular proteins, as well as cell death. 11,12,20,21 An in vitro proof of concept for photothermal imaging using targeted gold nanoparticles (GNPs) is demonstrated in this paper. By selectively increasing the temperature of GNPs that specifically target and decorate the surface of cancer cells, we can distinguish between cancerous and noncancerous cells (ie, normal background tissue).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the absorption properties of gold nanorods in the surface plasmon resonance wavelength are used to elevate temperature to 50°C and above, usually using lasers with a high optical output (above 10 W/cm 2 for about 20 minutes) in order to achieve effective denaturation and coagulation of cellular proteins, as well as cell death. 11,12,20,21 An in vitro proof of concept for photothermal imaging using targeted gold nanoparticles (GNPs) is demonstrated in this paper. By selectively increasing the temperature of GNPs that specifically target and decorate the surface of cancer cells, we can distinguish between cancerous and noncancerous cells (ie, normal background tissue).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Furthermore, gold nanoparticles have been investigated in various contexts in relation to cancer diagnosis and treatment, including as a delivery vehicle for several chemotherapeutic agents, as a contrast agent for enhanced imaging, and for thermal ablation therapy. [7][8][9][10][11] Utilizing the differential absorption coefficient of a high atomic number (Z) material, such as gold, compared with soft tissue has shown potential as a radiosensitizing strategy through increased local dose deposition as a result of the generation of Dovepress submit your manuscript | www.dovepress.com secondary electron species. [12][13][14] A tissue modeling study using gold foil reported a dose enhancement factor of 50 due to the production of secondary electrons generated from low-energy photon irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different cancer therapeutic strategies have focused on the use of gold nanoparticles including the targeted delivery of anti-cancer agents including methotrexate [5] tamoxifen [6] and oxaliplatin [7], radio frequency radiation [8], thermal ablation [9,10] and metal enhanced radiotherapy [11].…”
Section: Introductionmentioning
confidence: 99%